Perbandingan Pendidikan Islam Menurut Perspektif KH. Ahmad Dahlan dan KH. Hasyim Asy ’Ari - Wijayati, Ravina; Habibi, Muhammad Devy (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2021)
This research aims to find out Islamic education, Islamic education methods and compare the similarities and differences of Islamic education according to kh perspective. Ahmad Dahlan and KH. Hasyim Asy' ari, so the author found shortcomings and advantages in islamic education research according to both figures. The research method used in this research is a Library Research method that is a series of activities related to the method of collecting library information, reading and writing and processing research materials. The data analysis technique that the author used in this study is content analysis or often called content analysis. This content analysis is used to compare one research with other research that is in accordance with this article. It is a study that uses the source of literature from articles and journals to get research information. This research has a formulation of problems including How islamic education according to KH. Ahmad Dahlan and KH. Hasyim Asy' ari?, Share the Method of Islamic Education according to the Perspective of KH. Ahmad Dahlan and KH. Hasyim Asy' ari?, How does Islamic education compare according to kh perspective. Ahmad Dahlan and KH. Hasyim Asy' ari?. The results of this study define the education of the two figures and compare so that there are similarities and differences between the two figures and produce deficiencies and advantages in Islamic education according to the KH Perspective. Ahmad Dahlan and KH. Hasyim Asy' ari.